Rapid Early Triage by Leukocytosis and the Thrombolysis in Myocardial Infarction (TIMI) Risk Score for ST-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention: An Observational Study. Issue 7 (February 2016) - Yeh, Yen-Ting; Liu, Cheng-Wei; Li, Ai-Hsien; Ke, Shin-Rong; Liu, Yuan-Hung; Chen, Kuo-Chin; Liao, Pen-Chih; Wu, Yen-Wen
Abstract : Abstract: The clinical utility of leukocytosis in risk assessment for ST-elevation myocardial infarction (STEMI) is still unclear. We aim to demonstrate the prognostic value of leukocyte counts independent from traditional risk factors and the TIMI risk score (TRS) for STEMI and to propose a practical model comprising leukocyte count for early triage in STEMI undergoing primary angioplasty. A prospective database (n = 796) of consecutive STEMI cases receiving primary angioplasty at a tertiary medical center was retrospectively analyzed in the period from February 1, 2007 through December 31, 2012. Primary endpoints were 30-day and 1-year mortality. Propensity score-adjusted Cox regression models and subdivision analysis were performed. Leukocytosis group (n = 306) had higher 30-day mortality (5.9% vs 3.1%, P  = 0.048) and 1-year mortality (9.2% vs 5.1%, P  = 0.022). After adjustment by propensity score and TRS, leukocyte count (per 10 3 /μL) was an independent predictor of 1-year mortality (HR: 1.086, 95% CI: 1.034–1.140, P  = 0.001). Subdivision analysis demonstrated the correlation between leukocytosis and higher 1-year mortality within both high and low TRS strata (divided by 4, the median of TRS). Additionally, 24% (191 out of 796) of patients were characterized by nonleukocytosis and TRS < 4, having 0% of mortality rate at 1-year follow-up. In conclusion, leukocyte count is an independent prognostic factor adding incremental value to TRS for STEMI. Nonleukocytosis in conjunction with TRS < 4 identifies a large patient group at extremely low risk and thus provides rapid early triage for STEMI patients undergoing primary PCI. This finding is worth validation in the future.